Ethnic entrepreneurs and online home-based businesses: An exploratory study - Muhammad Naveed Anwarand; Elizabeth M. Daniel (Journal of Global Entrepreneurship Research, 2017)
This exploratory, qualitative study considers how online home-based businesses offer opportunities for ethnic entrepreneurs to 'break out' of traditional highly competitive and low margin sectors. Previous studies have found a positive association between ethnic minorities' high levels of entrepreneurship and home computer use in ethnic groups. Despite these associations, previous studies have overlooked the particular opportunities offered by home-based online businesses to ethnic entrepreneurs. The study adopts mixed embeddedness as a theoretical lens to guide interviews with 22 ethnic entrepreneurs who have started online home-based businesses in the UK. We find online home-based businesses offer ethnic entrepreneurs novel opportunities to draw on their ethnic advantages and address the constraints they face. The unique affordances of this type of business allow entrepreneurs to develop the necessary IT skills by self-learning and experimentation and to sub-contract more difficult or time consuming aspects to others. The findings also show that, consistent with the theory of mixed embeddedness, whilst the entrepreneurs are influenced by social, economic and institutional forces, online businesses allow them to exert their own agency and provide opportunities to uniquely shape these forces.
Keywords: 650; Ethnic entrepreneurship; Mixed embeddedness; Online home-based business